The octopamine receptor Octβ2R regulates ovulation in Drosophila melanogaster. - Junghwa Lim; Paul R Sabandal; Ana Fernandez; John Martin Sabandal; Hyun-Gwan Lee; Peter Evans; Kyung-An Han (PLoS ONE, 2014)
Oviposition is induced upon mating in most insects. Ovulation is a primary step in oviposition, representing an important target to control insect pests and vectors, but limited information is available on the underlying mechanism. Here we report that the beta adrenergic-like octopamine receptor Octβ2R serves as a key signaling molecule for ovulation and recruits protein kinase A and Ca(2+)/calmodulin-sensitive kinase II as downstream effectors for this activity. We found that the octβ2r homozygous mutant females are sterile. They displayed normal courtship, copulation, sperm storage and post-mating rejection behavior but were unable to lay eggs. We have previously shown that octopamine neurons in the abdominal ganglion innervate the oviduct epithelium. Consistently, restored expression of Octβ2R in oviduct epithelial cells was sufficient to reinstate ovulation and full fecundity in the octβ2r mutant females, demonstrating that the oviduct epithelium is a major site of Octβ2R's function in oviposition. We also found that overexpression of the protein kinase A catalytic subunit or Ca(2+)/calmodulin-sensitive protein kinase II led to partial rescue of octβ2r's sterility. This suggests that Octβ2R activates cAMP as well as additional effectors including Ca(2+)/calmodulin-sensitive protein kinase II for oviposition. All three known beta adrenergic-like octopamine receptors stimulate cAMP production in vitro. Octβ1R, when ectopically expressed in the octβ2r's oviduct epithelium, fully reinstated ovulation and fecundity. Ectopically expressed Octβ3R, on the other hand, partly restored ovulation and fecundity while OAMB-K3 and OAMB-AS that increase Ca(2+) levels yielded partial rescue of ovulation but not fecundity deficit. These observations suggest that Octβ2R have distinct signaling capacities in vivo and activate multiple signaling pathways to induce egg laying. The findings reported here narrow the knowledge gap and offer insight into novel strategies for insect control.